STUDENTS’ PERCEPTIONS ON THE USE OF OFFLINE-BASED LEARNING METHODS: LECTURE AND GROUP PRESENTATION IN ISLAMIC EDUCATION COURSE AT UNTAG SEMARANG - Diah Ayu Mawarti; Novita Al Ihyak Dieni; Wawan Wibisono (2024)
The application of a learning method in the learning process has an impact on students’ acceptance. This can be seen in the use of offline-based learning methods: lecture and group presentation in Islamic Religious Education (PAI) course at 17 Agustus 1945 Semarang University (Untag) in the 2021-2022 academic year in the odd semester. Students' perceptions of offline-based learning methods: lecture and group presentation in Islamic Education course were studied using a qualitative approach. Data collection techniques were conducted through interview, observation, documentation, and questionnaire. From the result of the interview, which was then related to the result of observation during the learning process and compared with the result of the questionnaire, it was seen that the use of offline-based learning methods: lecture and group presentation in PAI courses caused different perceptions among each student. The application of the lecture method through explaining the material from the lecturer makes it easier for them to understand the material rather than having to learn and explain it themselves. It is proven that 79.8% of students like the offline lecture method compared to group presentations. As many as 52.9% of students chose group presentations. The group presentation learning method can train them to actively discuss and hone public speaking. However, after attending PAI lectures, students gain insight into religious knowledge and will apply it in their daily lives.